HUBUNGAN UKURAN LINGKAR PINGGANG DENGAN TEKANAN DARAH PADA WANITA USIA SUBUR DI KELURAHAN RENGAS PULAU KECAMATAN MEDAN MARELAN KOTA MEDAN - IRFAN DARFIKA LUBIS; MUHAMMAD FAHRUR FAJZRI2 (JURNAL ILMIAH SIMANTEK, 2022)
The waist is a part of the human body which is located on a horizontal line between the costal arches and the iliac crest, the waist is in the abdominal region. Waist circumference is often used as an alternative marker of abdominal fat mass. Blood pressure is expressed as two levels of blood pressure, namely systolic pressure and diastolic pressure in mmHg. Normal blood pressure is stated when systolic <120 mmHg, diastolic, <80 mmHg. While blood pressure with systolic 120-139, diastolic 80-89 mmHg categorized as prehypertension, systolic blood pressure 140-159, diastolic 90-99 categorized as hypertension. This research is a descriptive analytic study with a cross sectional approach. The research subjects were 100 women of childbearing age living in Rengas Pulau Village, Medan Marelan Subdistrict, Medan City who met the inclusion and exclusion criteria. Waist circumference with systolic blood pressure has a significant correlation coefficient of 0.350 (p = 0.00). Waist circumference size with diastolic blood pressure has a significant correlation coefficient value of 0.400 (p = 0.085). Based on the results of this study, it can be concluded that there is a correlation between waist circumference size and systolic blood pressure in the direction of positive correlation with weak correlation strength while diastolic blood pressure with size Waist circumference is not correlated